2016
DOI: 10.1007/s10067-016-3198-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum osteoprotegerin with arterial stiffness, preclinical atherosclerosis, and disease activity in patients with ankylosing spondylitis

Abstract: Patients with ankylosing spondylitis (AS) reportedly have a higher mortality and morbidity risk. Osteoprotegerin (OPG) was recently defined as an important cardiovascular (CV) marker in the general population. We aimed to assess the relationship of serum OPG levels with arterial stiffness, carotid intima media thickness (CIMT), and clinical and laboratory data in AS patients. We examined 60 AS patients without CV disease or risk factors and 50 healthy controls. Disease activity was evaluated using the Bath Ank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…All of the 35 studies included in the meta-analysis were analyzed using the Stata 12.0 (Stata Corp, College Station, Texas) software. 5 -39 The values of continuous parameters (cIMT, PWV, FMD) were expressed as mean and standard deviation (SD). Median or interquartile range values were transformed into mean and SD forms.…”
Section: Methodsmentioning
confidence: 99%
“…All of the 35 studies included in the meta-analysis were analyzed using the Stata 12.0 (Stata Corp, College Station, Texas) software. 5 -39 The values of continuous parameters (cIMT, PWV, FMD) were expressed as mean and standard deviation (SD). Median or interquartile range values were transformed into mean and SD forms.…”
Section: Methodsmentioning
confidence: 99%
“…OPG was recently defined as an important cardiovascular (CV) marker in the general population with arterial stiffness, vascular calcification, and carotid intima media thickness [84]. OPG constitutes a novel biomarker with prognostic significance in patients with severe malaria.…”
Section: Opg In Cancers and Other Diseasesmentioning
confidence: 99%
“…13 In a study by Serdaro glu and colleagues, 14 carotid IMT and PWV values were found to be higher than the controls, and PWV values were substantially different between patients with AS with low and high disease activity. 14 Mathieu and colleagues 7 also reported higher carotid IMT and greater arterial stiffness in patients with AS than the controls, although the difference was not statistically significant. In another study, including age-and gender-matched AS patients and controls, normal IMT values were reported in AS patients, 1 and in a further study, PWV values were not found to be substantially different between patients with AS and healthy controls.…”
Section: Discussionmentioning
confidence: 94%
“…In a study by Serdaroğlu and colleagues, carotid IMT and PWV values were found to be higher than the controls, and PWV values were substantially different between patients with AS with low and high disease activity . Mathieu and colleagues also reported higher carotid IMT and greater arterial stiffness in patients with AS than the controls, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 96%